The Impact of Global Pressures on the Affective Well-Being of Australian Managers' Performance - Hosie, Peter; Forster, N.; Sevastos, Peter (School of Management, Curtin University of Technology, Perth, Western Australia and the Singapore Human Resources Institute, 2004)
Implicit in the drive for international competitiveness is the recognition that high-performing managers are essential for organisations to achieve and sustain competitive advantage. A critique is made of the global economic pressures impacting on Australian managers' jobs. Elements of affective well-being and intrinsic job satisfaction that predict managers' performance are identified. Recommendations are made about how managers' jobs might be changed to enhance, or to avoid a decline in, affective well-being, intrinsic job satisfaction and performance, in order to improve overall organisational effectiveness. The emphasis is on investigating an aspect of human behaviour with the potential to enhance managerial performance. Organisations have the potential to gain a competitive advantage through HRM initiatives, when these are derived from and integrated with organisational strategies.